ESTADO E TRABALHO: a regulamentação do trabalho no Brasil a partir de 1990 e a atuação da OIT - Caminha, Marco Aurélio Lustosa (2014)
This thesis analyzes the present conditions and prospects of state regulation of labor in Brazil, facing two determining facts: the current crisis of capitalism and the role of the ILO. Primarily, it discusses the main historical, philosophical and theoretical aspects that gave rise to the beginning of state interference in labor relations in the major capitalist countries, in comparison with the Brazilian case. Secondly, it analyzes the behavior of nation-states in the area of labor regulation in the context of the crisis of capitalism, focusing mainly on the productive restructuring of the 1980 s, supported by the neoliberalism and driven by the globalization of capital process with great repercussion in Brazil since the 1990 s. Consequently, key measures of deregulation and flexibilization of labor standards occurred in the advanced capitalist countries and in Brazil are contextualized and analyzed, being revealed the purposes of its defenders and the implications on the conditions of use and reproduction of the workforce. Finally, from the ILO s study and effectiveness of its work, it is demonstrated that the "standard" for social rights that ILO disseminates and enforces on its Member States, including Brazil, have an important role in the resistance against measures of deregulation as well as to the flexibilization of labour standards.